Conceptual Framework for Monitoring and Evaluation - Mackay, Keith (World Bank, Washington, DC, 2012)
This is the first note in a monthly series on government monitoring and evaluation (M&E) systems led by the PREM, or Poverty Reduction and Equity Management under the guidance of Jaime Saavedra, Gladys Lopez-Acevedo, and Keith Mackay, with contributions from several World Bank colleagues. The main purpose of this series is to synthesize existing knowledge about M&E systems and to document new knowledge on M&E systems that may not yet be well understood. The series targets World Bank other donor staff who are working to support client governments in strengthening their M&E systems, as well as government officials interested in learning about the uses and benefits of M&E and in adopting a more systematic approach toward M&E in their governments.